LincROR promotes tumor growth of colorectal cancer through the miR-145/WNT2B/WNT10A/Wnt/β-catenin regulatory axis - Deng, Li-Qiang; Li, Shi-Ying; Xie, Tian; Zeng, Wei-Qiang; Wang, Yu-Yan; Shi, Chuan-Jian; Jin-Fang, Zhang (PloS one, 2024)
Colorectal cancer (CRC) is a prevalent form of malignant tumor, and the current clinical treatments are far from satisfactory. Identifying new therapeutic targets is therefore essential for clinical practices. The long intergenic non-protein coding RNA lincROR has been shown to play a significant role in the tumorigenesis of various cancers. However, the molecular mechanism underlying lincROR-mediated CRC tumorigenesis remains unclear. In the present study, we found that knockdown of lincROR significantly inhibited cell viability in vitro , while its overexpression promoted tumor growth in vivo . Mechanistically, lincROR acted as a miRNA sponge for miR-145, thereby elevating the expression of the target genes WNT2B and WNT10A. The overexpression of WNT2B and WNT10A definitely activated the Wnt/β-catenin pathway, thus led to promoting tumorigenesis in CRC. In summary, our findings identified lincROR as a novel activator of the Wnt/β-catenin pathway by serving as a miRNA sponge for miR-145 and facilitating tumorigenesis, which suggests that lincROR may be a potential therapeutic target for CRC patients.